RELATIONSHIP BETWEEN SPIRITUAL INTELLIGENCE LEVEL AND COPING MECHANISM IN ADOLESCENTS - Vera Fauziah Fatah; Mayang Galuh Larasati; Desmaniarti Z; Rukman Rukman; Zaenal Muttaqin; Muryati Muryati (Poltekkes Kemenkes Bandung, 2025)
This research is based on the 2018 Riskesdas data, which shows an increase in the number of mental health disorders in adolescents over 15 years of age by 5.3% from 2013. Adolescence is a crucial period for a person's mental health, not all adolescents can manage their stress. In this condition, coping mechanisms are needed that aim to overcome stressors. Spiritual intelligence is one of the factors that impact adolescents in choosing coping efforts. Adolescents who have high spiritual intelligence will be able to choose constructive coping. The study aims to analyze the relationship between the level of spiritual intelligence and coping mechanisms in adolescents. This study is a cross-sectional study with a categorical analytical approach, located at SMAN 6 Bandung. The number of samples is 86 respondents who are selected using proportional stratified random sampling techniques. The instruments used in this study were a questionnaire on the level of spiritual intelligence adapted from King & DeCicco's theory, namely SISRI-24 (The Spiritual Intelligence Self Report Inventory), and coping mechanisms adapted from Carver & Cornor's theory, B-COPE (Brief from the Coping Orientation to Problem Experience). Furthermore, the data obtained were tested using the chi-square correlation test. The results of the statistical test on the relationship between spiritual intelligence and coping mechanisms in adolescents at SMA Negeri 6 Bandung obtained a p-value of 0.000 (p = 0.005), meaning that there is a relationship between the level of spiritual intelligence and coping mechanisms in adolescents at SMA Negeri 6 Bandung. There is a need to increase the consistency of the sustainability of existing spiritual guidance programs and enrich the material with more variety as an effort to improve adolescent coping mechanisms.